A SYSTEMATIC STUDY ON TALENT MANAGEMENT AND ITS EMERGING TRENDS @2020 - Datta, Angshupriya; Dsouza, Sarah; Anil Karande, Saylee (International Journal of Psychosocial Rehabilitation, 2020)
All organizations at the global level pay noticeable attention to the topic of talent management. Talent management means an ongoing strategy involving its high-quality staff to improve performance continually. It sacrifices an effective method of attracting and hiring people who have the right credentials, trains them to take top positions, reviews and tracks them, and prevents them from leaving the company. The aim of this research is to examine talent management strategies adopted by various organizations and to understand the role played by talent management in improving organizational performance. In order to manage these distinctive human assets, organisations. The present paper discusses the impact of talent management on the different dimensions of human resource functions through a systematic literature review.The results show that talent management systems are directly linked to organizational performance improvement and driving success. The paper also addresses emerging developments in talent management, which promote organizational processes in the execution of effective retention of talent.